Edukasi Pemanfaatan Buah Nanas sebagai Antioksidan untuk Meningkatkan Imunitas pada Remaja di MAN 1 Muaro Jambi - Maharani, Sri; Safitri, Safitri; Hayati, Fatihatul (Jurnal Abdimas Kesehatan (JAK), 2024)
Adolescents are in a transition period from childhood to adulthood. Physically, teenagers can be said to be mature but psychologically or mentally immature. Jambi Province is 8.2% for the prevalence of thinness in adolescents aged 16-18 years. The importance of consuming nutritious foods has an impact on adolescent health in the future. Lack of consumption of fruit and vegetables can result in various impacts, namely decreased immunity, such as getting flu easily, easily experiencing stress or depression, high blood pressure, digestive disorders such as constipation, bleeding gums, mouth ulcers, eye problems, wrinkled skin, arthritis, osteoporosis, acne, excess blood cholesterol, and cancer. The nutritional content contained in pineapple includes vitamins B6, B1 and vitamin C as well as folic acid. The sugar content is quite high and has the highest ability to act as an antioxidant to fight free radicals. The aim of the community service that will be carried out is to provide education about the use of pineapple as an antioxidant to increase immunity in teenagers. The methods for this community service activity are giving a post test before counseling is carried out, giving booklets, providing counseling to teenagers, conducting questions and answers and giving a pretest after the counseling is carried out. This Community Service will be carried out in June 2024 for 26 teenagers at MAN 1 Muaro Jambi. The community service that has been carried out has resulted in an increase in knowledge about the use of pineapple as an antioxidant to increase immunity in teenagers. The target output from this community service activity is in the form of scientific articles which will be submitted to national journals and can be used as products to enhance entrepreneurship.